With Good Heart - Painter, Muriel Thayer (University of Arizona Press, 2024)
Muriel Painter's account of Yaqui beliefs and ceremonies is based on her firsthand observations over the course of four decades. By the time Painter died in 1974, she was as familiar with Yaqui culture as on outsider could be and left behind the manuscript from which this volume arose. It was reviewed before the original publication in 1986 by a Yaqui committee and edited for publication by Edward Spicer.